2005
DOI: 10.1080/00207540512331311813
|View full text |Cite
|
Sign up to set email alerts
|

A review of gripping and manipulation techniques for micro-assembly applications

Abstract: This paper provides a review of micro-assembly-related research activities and their findings. The assembly of micro-devices involves handling of parts that are extremely small (in the order of 10 À6 m). Part designs, which are complex in shape and require the use of material of varying properties, cannot be manufactured using Micro-Electro Mechanical Systems (MEMS) technology; in such situations, assembly of micron-sized parts is necessary. Gripping techniques using micro-grippers and other manipulation/assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…If, in an attempt to release the particle, one charges the particle, forces vibration of the surface in question, etc., the released particle might move in an uncontrollable way leaving the observation field of the apparatus controlling the performance of the operation. That is the main reason why the handling, feeding, trapping and fixing of micro-and/or nano-particles is still the main bottleneck in micro manufacturing and is far from being solved in a satisfactory fashion [26]. Thus, formalizing the above, one of the main problems in the micro-and nanoassembly is the precise and reliable manipulation of a microor nano-particles that includes moving it from a given starting point, where it is to be taken from, to some end point, when it is to be placed on.…”
Section: Introductionmentioning
confidence: 99%
“…If, in an attempt to release the particle, one charges the particle, forces vibration of the surface in question, etc., the released particle might move in an uncontrollable way leaving the observation field of the apparatus controlling the performance of the operation. That is the main reason why the handling, feeding, trapping and fixing of micro-and/or nano-particles is still the main bottleneck in micro manufacturing and is far from being solved in a satisfactory fashion [26]. Thus, formalizing the above, one of the main problems in the micro-and nanoassembly is the precise and reliable manipulation of a microor nano-particles that includes moving it from a given starting point, where it is to be taken from, to some end point, when it is to be placed on.…”
Section: Introductionmentioning
confidence: 99%
“…Adhesive forces hold particles firmly on a carrier, irrespective of their arrangement. In contrast to handling particles using aspirating nozzles, or electric or magnetic forces, [16] adhesion is a robust and technically simple approach that is compatible with very small particles. Well-defined particle surfaces allow the creation of an adhesion cascade, such that particles can be transferred from surface to surface, exploiting the increasing adhesion.…”
mentioning
confidence: 99%
“…Consequently, their study is crucial vis-a`-vis potential engineering applications in the near future. A comprehensive literature review of research efforts dealing with the micro-assembly domain can be found in [15].…”
Section: Literature Reviewmentioning
confidence: 99%